A hyaluronic acid nanogel for photo–chemo theranostics of lung cancer with simultaneous light-responsive controlled release of doxorubicin1. Issue 24 (28th June 2015) - Khatun, Zehedina; Nurunnabi, Md; Nafiujjaman, Md; Reeck, Gerald R.; Khan, Haseeb A.; Cho, Kwang Jae; Lee, Yong-kyu
<x xml:space="preserve">Abstract</x> The nanogel composed of photo-/chemo-therapeutic agents having active targeting properties to specific cell and release of anticancer drug was controlled by laser irradiation.